Measurement of the B[bar]0-B0 and B[bar]s0-Bs0 production asymmetries in pp collisions at √s=7 TeV - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physics letters, 2014)
The B¯0-B0 and B¯s0-Bs0 production asymmetries, AP(B0) and AP(Bs0), are measured by means of a time-dependent analysis of B0→J/ψK⁎0, B0→D−π+ and Bs0→Ds−π+ decays, using a data sample corresponding to an integrated luminosity of 1.0 fb−1, collected by LHCb in pp collisions at a centre-of-mass energy of 7 TeV. The measurements are performed as a function of transverse momentum and pseudorapidity of the B0 and Bs0 mesons within the LHCb acceptance. The production asymmetries, integrated over pT and η in the range 4<pT<30 GeV/c and 2.5<η<4.5, are determined to be AP(B0)=(−0.35±0.76±0.28)% and AP(Bs0)=(1.09±2.61±0.66)%, where the first uncertainties are statistical and the second systematic.